Emotionally Negative Pictures Enhance Gist Memory - Bookbinder, S. H. (Emotion, 2016)
In prior work on how true and false memory are influenced by emotion, valence and arousal have often been conflated. Thus, it is difficult to say which specific effects are due to valence and which are due to arousal. In the present research, we used a picture-memory paradigm that allowed emotional valence to be manipulated with arousal held constant. Negatively-valenced pictures elevated both true and false memory, relative to positive and neutral pictures. Conjoint recognition modeling revealed that negative valence (a) reduced erroneous suppression of true memories and (b) increased the familiarity of the semantic content of both true and false memories. Overall, negative valence impaired the verbatim side of episodic memory but enhanced the gist side, and these effects persisted even after a week-long delay.